Cryodehydration Technique Applied to Anatomical Segments - Teixeira Filho, Althen; Schäfer, Bárbara Tavares; Vives, Patrícia Silva (Journal of Morphological Sciences, 2019)
Introduction The present study describes a variation of the cryodehydration technique, applied to prepare biological tissues by repetitions of section freezing and thawing (SFT). First developed for muscles and then viscera, the aim of this process as presented here is to obtain anatomical segments to be used in anatomy classes, general exhibitions and museums.Materials and Methods The animal, previously fixed in 10% formalin, must be frozen and then sectioned in longitudinal, transverse and horizontal slices of the body-axis. It has two steps: the “burning phase,” in which ice crystal formation and water dilatation cause micro ruptures in the tissue; and the “dehydration phase,” developed to dry out the slices segments slowly and, at the same time, to impregnate tissues with wood glue.Results The obtained slices present several advantages, such as being dry segments, of light weight, and being rapidly used, easily stored and promptly studied. Also, it is possible to study the different organs of one segment and, by apposition, remount an entire animal, enabling a dynamic study.Conclusion This very simple and inexpensive technique produces anatomical preparations with high durability and resistance, which are very helpful in practical and theoretical classes.
Keywords: anatomical technique; cryodehydration technique; anatomical slices